Mass moralizing : marketing and moral storytelling - Hopkins, Phil, 1958- (Rowman & Littlefield, 2015)
Drawing from sources as diverse as Plato, Marshal McLuhan, and McDonald's, Mass Moralizing makes the intriguing case that contemporary marketing has moved beyond merely selling commodities and now seeks to turn our values themselves into commodities. It sheds light on a subtle but important new concern about the ever-shrinking difference between human values and consumer values.